Workshop Implementasi Kepmendikbudristek No. 262/M/2022 Tentang Kurikulum Merdeka (IKM) di MI Bahrul Ulum dan SDN Kaligerman - Brik Kumala; Zanuba Arifah Khofshoh; Intan Fatika Sari; Ayu Nur Sholehah; Muhammad Ilyasa Abdullah; Surti Wulandari; Siti Fatimah (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
The Merdeka Curriculum focuses on essential material and on developing the character of the Pancasila Student Profile. The Merdeka Curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to explore concepts and strengthen competencies. In the learning process, teachers have the freedom to choose various learning tools so that learning can be tailored to the learning needs and interests of students. In this curriculum there is a project to strengthen the achievement of the Pancasila student profile. Then, it is developed based on certain themes determined by the government. The current project does not aim to achieve certain learning achievement targets, so it is not tied to subject content. Before the curriculum is implemented, regular reviews are needed to find out whether the dynamics of development in the scientific fields are outlined and curriculum developers need to carry out a careful analysis and then draw up a plan. learning by determining models and organizing learning strategies and implementing them into the Teaching and Learning Process (PBM).